Withdrawal of Continuous Positive Airway Pressure Therapy for 2 Weeks in Obstructive Sleep Apnoea Patients Results in Increased Circulating Platelet and Leucocyte-Derived Microvesicles. - Ayers, L; Turnbull, C; Petousi, N; Ferry, B; Kohler, M; Stradling, J (Karger Publishers, 2016)
In 2013 we reported that in patients with obstructive sleep apnoea (OSA), withdrawing their continuous positive airway pressure (CPAP) therapy for two weeks led to a significant increase in endothelial cell-derived microvesicles (MVs) [1]. Several other studies have found that the initiation of CPAP therapy in patients with OSA leads to a fall in endothelial [2, 3] and platelet [4, 5] MVs, but there have been no further studies investigating the impact of CPAP withdrawal in patients established on therapy, which provides a more robust experimental protocol. Therefore in this further exploratory study we have examined the impact of CPAP withdrawal on other subtypes of MVs.